Transcriptome analysis of Sclerotinia ginseng and comparative analysis with the genome of Sclerotinia sclerotiorum. (April 2019) - Wang, Dan; Fu, Junfan; Zhou, Rujun; Li, Zibo; Han, Yueling; Liu, Xinran
Abstract: Sclerotinia ginseng is a non-model necrotrophic pathogen responsible for a serious epidemic in the ginseng production area in northeast China. In this study, de novo RNA sequencing was carried out using an Illumina HiSeq ™ 4000 platform in conjunction with the short-read assembly program Trinity. The S. ginseng transcriptome was compared with that of Sclerotinia sclerotiorum, and species-specific unigenes were annotated with KEGG and GO terms. Phylogenetic analysis of amino acid sequences for four polygalacturonase ( pg ) genes and a pH-response transcription factor ( pac1 ) homologous gene identified in S . ginseng revealed a close evolutionary relationship with other species of Sclerotiniaceae. Highlights: De novo sequencing of Sclerotinia ginseng by using Illumina HiSeq™ 4000. Comparing with Sclerotinia sclerotiorum, species specific unigenes were analyzed. A phylogenetic analysis of four pg genes and two pac1 homologous genes.